FORMATION OF PSYCHOLOGICAL THINKING IN THE STUDY OF LATIN LANGUAGE IN MEDICAL HIGHER EDUCATION INSTITUTIONS - Sabirova Sabina Olimovna (Web of Journals Publishing, 2025)
This article discusses the development of psychological thinking of medical students and the methods of using various concepts in teaching Latin.
Keywords: Thinking, idea, concept, aesthetic values.